Editorial - Ghosh, Bikramaditya (Ushus Journal of Business Management, 2020)
We are all homebound in a global village, owing to the novel coronavirus or Covid-19. This is indeed a special version of Ushus-Journal of Business Management. I wish safety and good health to one and all. Let almighty bless us.This issue is quite unique in terms of coverage. It covers wide variety of quantitative finance aspects.